Design of A Smartphone-Based Self-Service Patient Kiosk Application at Bhayangkara Hospital Bengkulu - Reka Dwi Syaputra; Nofri Heltiani; Agusianita Agusianita (Jurnal Infokes, 2026)
Background: The manual outpatient registration process at Bhayangkara Level III Hospital Bengkulu leads to long queues and high waiting times, thus necessitating a technological solution. Objective: This study aims to design a smartphone-based Self-Service Patient Kiosk (APM) for outpatient polyclinics using Waterfall. Methods: This descriptive qualitative research with a software engineering approach applies Waterfall stages: requirements analysis, system design, interface design, and prototyping. Data were collected through observation, interviews, checklists from 11 officers, and system validation using UAT on 7 features, generating 77 responses. Results: Results showed 66 responses (85%) needed, and 11 (15%) not needed. The resulting APM prototype includes features for self-patient data input, polyclinic and doctor selection, appointment scheduling, digital queue printing, and real-time queue monitoring. The prototype has a user-friendly interface and integrates with patient registration digitalization. Conclusion:  In conclusion, the smartphone-based APM effectively accelerates and decentralizes the registration process. Suggestion: Future researchers should proceed to coding, SIMRS integration, and direct field testing.